2004
DOI: 10.1002/ffj.1365
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the leaf and fruit essential oils of Murraya paniculata (L.) Jack. (Syn. Murraya exotica Linn.)

Abstract: The essential oils from the leaves and fruits of Murraya paniculata (L.) Jack. grown in Nigeria were analysed by means of gas chromatograph and gas chromatograph interfaced with mass spectrometry. Both oils were rich in sesquiterpenoids. The principal constituents of the leaf oil were β β β β β-cyclocitral (22.9%), methyl salicylate (22.4%), trans-nerolidol (11.7%), α α α α α-cubebene (7.9%), (− − − − −)-cubenol (6.8%), β β β β β-cubebene (5.8%) and isogermacrene (5.7%). The most abundant constituent of the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 7 publications
3
32
0
1
Order By: Relevance
“…1,14,15 Again, the variability can be particularly evident in entomophilous ½owers, where volatiles can function as orientation clues, and thus the volatiles emitted by the ½owers or ½ower parts are distinct from those of the other plant parts. Kuropka et al 16 showed that in Achillea ptarmica the monoterpenes were almost non-existent in oils from the green parts and roots, while the contrary happened in the ½owers.…”
Section: Type Of Plant Materialsmentioning
confidence: 99%
“…1,14,15 Again, the variability can be particularly evident in entomophilous ½owers, where volatiles can function as orientation clues, and thus the volatiles emitted by the ½owers or ½ower parts are distinct from those of the other plant parts. Kuropka et al 16 showed that in Achillea ptarmica the monoterpenes were almost non-existent in oils from the green parts and roots, while the contrary happened in the ½owers.…”
Section: Type Of Plant Materialsmentioning
confidence: 99%
“…The dried leaves of Murraya exotica L. as traditional Chinese medicine listed in the Chinese Pharmacopoeia (2015 Edition), have been widely used for the treatment of traumatic injury, stomachalgia, toothache, and rheumatic arthralgia . Hainanmurpanin ( 1 ), meranzin ( 2 ), and phebalosin ( 3 ) are three main coumarins in the M. exotica L. , and their chemical structures are shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain as many fragment ions as possible, the peaks detected with intensity over 10,000 were selected for identification. The chemical formulas for all parent and fragment ions of the selected peaks were calculated from the accurate mass using a formula predictor by setting the parameters as follows: C (0-30), H (0-50), O (0-20), S (0-4), N (0-4), Cl (0-4) and ring double bond (RDB) equivalent value [0][1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Other elements such as P and Br were not considered as they are rarely present in the complex matrix.…”
Section: Data Processingmentioning
confidence: 99%
“…Phytochemical investigations have revealed that flavonoids, coumarins and essential oils are the main constituents of M. paniculata [1][2][3]. Polymethoxylated flavonoids (PMFs), a special…”
Section: Introductionmentioning
confidence: 99%